Apatinib + CPT-11 + S-1 for treatment of refractory brain metastases in patient with triple-negative breast cancer: Case report and literature review. Issue 15 (April 2018) - Hu, Ting; Liu, Cuiwei; Li, Qiuhui; Xiong, Jie; Ma, Yuxi; Wu, Gang; Zhao, Yanxia
Abstract: Rationale: Brain metastasis (BM) is a rising challenge in forward-looking oncology, as its treatment choices are very limited, especially, after the failure of local treatment schemes. Patient concerns: We report on a 39-year-old Chinese woman who was diagnosed with stage IV triple-negative breast cancer(TNBC) with multiple brain, lung, and bone metastases. She had previously, undergone whole-brain radiation therapy. Paclitaxel, platinum, UTD1, capecitabine, gemcitabine, vinorelbine, and single-agent apatinib were then administered as first- to fifth-line therapies. She exhibited progression each time after a short period of disease stabilization. Diagnoses: Triple-negative breast cancer. Interventions: The patient chose treatment with apatinib+CPT-11+S-1 as the sixth-line therapy. Outcomes: A remarkable response of the brain, and lung metastases, and alleviation of the brain edema were achieved, and these effects persisted for 7 months. Lessons: We describe the significant anti-tumor effect of apatinib + CPT-11 + S-1 against BMs from breast cancer. This report is the first to suggest potential approaches to BM treatment using this scheme and describes the effects of an apatinib-containing regimen on BMs.